CD4 LYMPHOCYTE IN HIV / AIDS BEFORE AND AFTER ANTIRETROVIRAL THERAPY - Prabowo, Rangsang Bagus; Pertiwi, Dewi Indah Noviana; Hendriyono, FX. (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: Human Immunodefficiency Virus (HIV) is a virus that decreases the human immunity system, therefore the infected people become susceptible to any kind of infections. Examination of CD4 lymphocyte count periodically is one of the antiretroviral therapy success indicators. The purpose of this research was to determine the difference of CD4 lymphocyte count before and after antiretroviral therapy at Ulin General Hospital Banjarmasin on 2013-2015. The method of this research was observational analytic with cross-sectional approach. The study population was 55 patients which were selected by inclusion and exclusion criteria. Results portrayed an increase of the CD4 lymphocyte count in 51 patients after being given four kinds of antiretroviral for 6 months with the mean increase in CD4 lymphocyte count was 92,72 cell/ÂµL. Data analysis result with Wilcoxon test portrayed a difference of the CD4 lymphocyte count before and after antiretroviral therapy with p value=0,000. In conclusion, there was a significant difference of the CD4 lymphocyte count before and after antiretroviral therapy.Â Keywords: Human Immunodeficiency Virus, CD4, lymphocyt, antiretroviral therapy